2023
DOI: 10.1002/adom.202300414
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance and Stability of CsPbBr3/WSe2 Hybrid Photodetectors Functionalized Using Quaternary Ammonium Ligands

Abstract: The 2D–0D hybrid photodetector, with its special structure, high sensitivity, and wavelength tunability, is reported as a promising candidate system for optoelectronic devices. As research on hybrid lead halide perovskite quantum dots (PQDs) has progressed, PQDs with high photoluminescence (PL) quantum yield and excellent absorption properties are increasingly applied in optoelectronic devices; however, PQD stability remains one of the biggest limitations on device performance. Here, it is reported that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…164,165 The colloidal stability of the PQDs could also decrease as a result of the bonding of labile ligands to the surface atoms of PQDs, which gives rise to surface trap sites. 166 Therefore, in order to solve these urgent issues, Moon et al 167 recently proposed a surface passivation strategy to improve the stability of CrPbBr 3 PQDs while optimizing optical properties. The quaternary ammonium ligand (didodecyldimethylammonium bromide, DDAB) was employed to inhibit the proton transfer between OLA and OA, thereby effectively passivating the surface of CrPbBr 3 PQDs.…”
Section: Pds Based On Qds/tungsten-based 2d Materials Heterostructurementioning
confidence: 99%
“…164,165 The colloidal stability of the PQDs could also decrease as a result of the bonding of labile ligands to the surface atoms of PQDs, which gives rise to surface trap sites. 166 Therefore, in order to solve these urgent issues, Moon et al 167 recently proposed a surface passivation strategy to improve the stability of CrPbBr 3 PQDs while optimizing optical properties. The quaternary ammonium ligand (didodecyldimethylammonium bromide, DDAB) was employed to inhibit the proton transfer between OLA and OA, thereby effectively passivating the surface of CrPbBr 3 PQDs.…”
Section: Pds Based On Qds/tungsten-based 2d Materials Heterostructurementioning
confidence: 99%
“…For example, Moon et al reported a surface passivation strategy using quaternary ammonium ligands (docosenyl dimethylammonium bromide, DDAB) to improve the performance and stability of CsPbBr 3 •PQDs. 30 Unfortunately, the surface-modified CsPbBr 3 •PQDs water stability test was conducted for only 16 h, and it cannot be demonstrated that it has long-term water stability that can improve practical applications. A large improvement in water stability can usually be obtained by using the coating method.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, this method has limited stability improvement for QDs in water, and relatively few reports have been reported. For example, Moon et al reported a surface passivation strategy using quaternary ammonium ligands (docosenyl dimethylammonium bromide, DDAB) to improve the performance and stability of CsPbBr 3 ·PQDs . Unfortunately, the surface-modified CsPbBr 3 ·PQDs water stability test was conducted for only 16 h, and it cannot be demonstrated that it has long-term water stability that can improve practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Proof-of-concept double-sided imaging has been realized based on two kinds of electronic eye prototypes (concave and convex hemispheres) in a single device configuration. Thus far, researchers have developed numerous photodetectors based on various 2DLMs spanning elemental semiconductors/semimetals [68][69][70][71][72], chalcogenides [73][74][75][76][77][78][79][80][81][82][83], nitrides [84], multi-elemental semiconductors [85][86][87][88][89][90][91][92], etc.…”
Section: Introductionmentioning
confidence: 99%